Multi-Scale Light-Sheet Fluorescence Microscopy for Fast Whole Brain Imaging - Zhang, Zhouzhou; Yao, Xiao; Yin, Xinxin; Ding, Zhangcan; Huang, Tianyi; Huo, Yan; Ji, Runan; Peng, Hanchuan; Guo, Zengcai V. (Frontiers in Neuroanatomy, 2021)
Whole-brain imaging has become an increasingly important approach to investigate neural structures including somata distribution, dendritic morphology and axonal projection patterns. Different structures require whole-brain imaging at different resolutions. Thus it is extremely desirable to perform whole-brain imaging at multiple scales. Imaging a complete mammalian brain at synaptic resolution is challenging as it requires continuous imaging from days to weeks due to the large number of voxels to sample. And it is also difficult to acquire constant quality of imaging due to light scattering during in toto imaging. Here, we reveal that light-sheet microscopy has unique advantage over widefield microscopy in multiscale imaging due to its decoupling of illumination and detection. Based on this observation, we have developed a multiscale light-sheet microscope that combines tiling of light-sheet, automatic zooming, periodic sectioning and tissue expansion to achieve constant quality of brain wide imaging from cellular to sub-micron spatial resolution rapidly (all within a few hours). We demonstrated the strength of our system by testing it using mouse brains prepared using different clearing approaches, and were able to track electrode tracks as well as axonal projections at sub-micron resolution to trace the full morphology of single mPFC neurons that have remarkable diversity in long-range projections.